RELATIONSHIP OF CHARACTERISTICS OF MUSCULAR COORDINATION, BALANCE AND THE OF THE VEGETATIVE-VASCULAR DEPENDENTS ON DANCERS - Yu. P. Bredikhina; L. V. Kapilevich (Бюллетень сибирской медицины, 2013)
Study the relation between the characteristics of muscle coordination, balance, and - vegetative-vascular balance on dancers. The dependence of balance and coordination abilities of the nature of the muscle and, in turn, from the vegetative-vascular support activities. The method of correlation analysis were confirmed by the relationship of coordination abilities with the characteristics of the bioelectrical activity of the muscles and vegetative-vascular support. All the above allows us to consider the formation of skills in ballroom dancing as a single functional system, in which the sense of balance and coordination abilities that determine the skill level of athletes associated with the information field of visual and vestibular reception, to the organization of the contractile activity of muscles and vegetative-vascular maintenance activities.